1987
DOI: 10.1007/bf00014522
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a toxic water-bloom of Microcystis aeruginosa (Cyanophyceae) in Lake Akersvatn, Norway

Abstract: During the summer and fall of 1984 and 1985, the eutrophic Lake Akersvatn in south-eastern Norway, used as reserve drinking water reservoir, was found to produce heavy water-blooms of the colonial blue-green alga Microcystis aeruginosa. Samples of the water-bloom were found to be toxic using the mouse bioassay. No toxin was found free in the water as detected by HPLC and mouse bioassay. The toxic cells (minimum lethal dose 8-15 mg/kg body weight in mice) and purified toxin (minimum lethal dose 50 µg/kg body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…It has generally been found that 50-75% of bloom isolates are capable of producing toxins, with often more than one toxin (e.g., MCs and anatoxin-a) and several MC congeners being simultaneously produced. Concentrations of more than 24,000 Ag MCs/l have been reported from the shores of the Havel River, Berlin, Germany (Fastner et al, 1999) and Lake Akersvatn, Norway (Berg et al, 1987). Germany could exemplify for the widespread occurrence of toxic cyanobacterial blooms as documented in the literature (Wiedner et al, 2001).…”
Section: Microcystin: Risk Assessment and Guidance Values For Variousmentioning
confidence: 90%
“…It has generally been found that 50-75% of bloom isolates are capable of producing toxins, with often more than one toxin (e.g., MCs and anatoxin-a) and several MC congeners being simultaneously produced. Concentrations of more than 24,000 Ag MCs/l have been reported from the shores of the Havel River, Berlin, Germany (Fastner et al, 1999) and Lake Akersvatn, Norway (Berg et al, 1987). Germany could exemplify for the widespread occurrence of toxic cyanobacterial blooms as documented in the literature (Wiedner et al, 2001).…”
Section: Microcystin: Risk Assessment and Guidance Values For Variousmentioning
confidence: 90%
“…The freeze-dried algae was added once to the test aquaria at the beginning of each experiment. The initial concentrations of cells were calculated to approximate those encountered in water and in scum (~109-1012 cells/L) during M. aeruginosa blooms (Berg et al, 1987;Zohary and Madeira, 1990;Watanabe et al, 1992). The corresponding initial toxin concentrations (Table 1) were in the same range as those of oscillatoria toxin encountered during Oscillatoria agardhii blooms where fish mortality was reported Lindholm, 1990).…”
Section: Exposure To Waterborne Algaementioning
confidence: 99%
“…Blooms of cyanobacteria have been repeatedly associated with eutrophication processes (Berg et al 1987, Carmichael et al 1988, Druvietis 1997, Pinckney et al 1998, Codd 2000, Chorus 2005). Factors such as high water retention time in lakes and reservoirs, increased temperature, low N:P ratio, as well as surface radiation and wind conditions have been reported to influence bloom development (Carmichael 1996, Kononen et al 1996, Kawara et al 1998, Chorus & Bartram 1999.…”
Section: Introductionmentioning
confidence: 99%